The Effect of the Mindfulness Based Intervention Programme on the Adjustment of the Secondary School Student: Examining the Impact of Mindfulness Based Intervention on Secondary School Students' Adjustment (Journal of Advances and Scholarly Researches in Allied Education, 2017)
The Present study was conducted to explore the effect of Mindfulness based Intervention on the adjustment of School going children in terms of home, health, emotional and adjustment. The pre-test -post- test treatment design was applied on the experimental and control group of the participants. In total, 108 students from the four school of the city who gave their self-consent along with the consent of their parents to participate in the study were selected and further 54 each was selected randomly in the experimental and control group. Bell Adjustment Inventory (Hindi Version by Mohsin-Shamshad, 1987) was used in the present study to take the observation of the participants on their overall adjustment in terms of its four dimensions. The result was analyzed with the help of analysis of covariance and showed the significant difference between the scores of the participants on their posttest on their overall adjustment in terms of home, health, emotional and social adjustments of the participants of the experimental group than their counter group. The mean value of the experimental group turned out higher than the control group i.e., significant reduction was observed in the experimental group on their adjustment in terms of its four factors after the intervention.